Morpho-biological characteristics of the development of Viscum album in the conditions of the urbanized environment of Vinnytsia, Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Questions: Does the urbanized environment affect the morpho-biological characteristic of the development of Viscum album? Locations: Vinnytsia, Ukraine. Methods: route studies, mapping, photofixation, morpho-biological research methods. Nomenclature: Mosyakin & Fedoronchuk (1999) Results: The spread of Viscum album L. in Ukraine raises serious concerns among researchers. The excessive presence of Viscum album in urban tree stands leads to a loss of ornamental value, branch brittleness, drying out of branches, and a reduction in tree longevity. This is especially dangerous during the autumn-winter and winter-spring periods, when the branches of affected trees become brittle, prone to icing, and create hazardous conditions due to their fragility. Additionally, it can lead to the mass infestation of trees by pathogenic microorganisms and xylotrophic fungi spores. In Vinnytsia, a significant portion of parks, streets, and intra-block plantings are affected by Viscum album. We studied the spread and morpho-biological stages of Viscum album development on various tree species, namely: Acer platanoides, A. campestre, Acer negundo, Acer pseudoplatanus, Betula pendula, Fraxinus excelsior, Malus domestica, Malus niedzwetzkyana, Populus nigra, P. alba, Prunus cerasifera, Populus tremula, Robinia pseudoacacia, Salix alba, Sorbus aucuparia, Tilia platyphyllos and T. cordata. The spread of Viscum album depends on the age of the tree, its species, and the presence of birds. Conclusions: We identified all the main phases of development – from seed germination to fruit maturation, as well as the formation of new infestations through vegetative reproduction. Given the high degree of bird migration through Vinnytsia, the spread of Viscum album occurs in certain areas within a relatively short period. Furthermore, the regeneration of Viscum album predominantly occurs through the formation of new shoots on affected plants.
Keywords: mistletoe, hemiparasite, morphology, stages of development, haustoria